Body condition scoring of Bornean banteng in logged forests. Issue 1 (December 2016) - Prosser, Naomi; Gardner, Penny; Smith, Jeremy; Goon Ee Wern, Jocelyn; Ambu, Laurentius; Goossens, Benoit
Abstract Background The Bornean banteng (Bos javanicus lowi) is an endangered subspecies that often inhabits logged forest; however very little is known about the effects of logging on their ecology, despite the differing effects this has on other ungulate species. A body condition scoring system was created for the Bornean banteng using camera trap photographs from five forests in Sabah, Malaysia, with various past and present management combinations to establish if banteng nutrition suffered as a result of forest disturbance. Results One hundred and eleven individuals were photographed over 38, 009 camera trap nights from April 2011 to June 2014 in five forests. Banteng within forests that had a recent history of reduced-impact logging had higher body condition scores than banteng within conventionally logged forest. Conversely, when past logging was conducted using a conventional technique and the period of forest regeneration was relatively long; the banteng had higher body condition scores. Conclusion The body condition scoring system is appropriate for monitoring the long-term nutrition of the Bornean banteng and for evaluating the extent of the impact caused by present-day reduced-impact logging methods. Reduced-impact logging techniques give rise to individuals with the higher body condition scores in the shorter term, which then decline over time. In contrast the trend is opposite for conventional logging, which demonstrates the complex effects of logging on banteng body condition scores. This is likely to be due to differences in regeneration between forests that have been previously logged using differing methods.